Conceptual design of collaborative virtual environments for education using a theater-based metaphor - Alberto Bucciero; Anna Lisa Guido; Luca Mainetti (European Alliance for Innovation (EAI), 2011)
Collaborative Virtual Environments (CVEs) are becoming more and more important in many areas because they offer users the opportunity to experiment with novel interaction paradigms in order to perform collaborative work or have engaging experiences 'being together'. One of the most promising application fields is eLearning, where CVEs give the unique opportunity to explore effective educational formats. Surprisingly, if compared with other more traditional fields as software engineering and database, we note a lack of design approaches. We point out that a well-founded design approach is crucial to develop collaborative experiences that could generate substantial and measurable educational benefits. To meet this challenge, in this paper we present a set of founding concepts that enable pedagogs and teachers designing effective 3D virtual worlds for education. To keep our concepts simply understandable, we based our design method on a widespread metaphor: the theater. We demonstrate through a real case study the promising advantages of our approach: expressiveness to capture collaborative features at a high level of abstraction, semi-formality to facilitate the establishment of a common ground between educational designers and CVEs engineers, and guidance to enable non-experts to cope with all the relevant aspects of a 3D virtual world.